PENAMBAHAN JUS DAUN SIRIH (Piper bettle linn ) TERHADAP BOBOT BADAN AYAM BROILER - Anang Widigdyo (AVES: Jurnal Ilmu Peternakan, 2016)
Rapid growth rate in broilers is always followed by a rapid fatty liver, in which fat storage tends to increase with increasing body weight. The rapid growth in broilers that are often followed by a fatty is higher, it becomes a problem for consumers who want a chicken with a low fatty. The purpose of this study was to determine the effect of adding the juice of betel leaves to body weight of broiler chickens. This research was conducted in 9 March to 6 April 2014 for 28 days at Hamlet Village Kedungrejo Salamrejo Binangun District of Blitar. This research used an experimental method that uses a completely randomized design (CRD) using 4 treatments with 5 replicates, each replicate consisting 5 Broiler. The Results showed the treatment had no significant effect (P = 0.05) on body weight. Based on statistical calculations did not show any differences. The absence of significant differences is due to the weight of the chicken that uniform between treatments and content of feed used primarily energy and protein in the diet is almost the same.Keyword : Betlle Leaf Juice, Broiler Again, FCR